An investigation of how newly appointed team leaders in an automotive manufacturing organisation experience the role transition from specialists to team leaders - Mzelemu, Patrick Sbusiso (Rhodes University, Faculty of Commerce, Rhodes Business School)
The purpose of this study is to investigate and understand how specialists who are newly appointed team leaders in an automotive manufacturing organisation experience the transition from specialists to team leaders. The role of leading others in an organisation is linked to human resource leadership. The human resource is highlighted as a valuable resource as it is the only thinking resource in an organisation. It also influences cost and quality and it is central to the organisation's competitive advantage. Consequently, any interruptions or lack of effective management of the human resource will result in a loss of value that the human resource brings into the organisation since they maximise the use of all other resources. The role transitioning process takes place in three phases. These are the separation, transitioning and incorporation phases. In the separation phase, the transitioning individuals have difficulty detaching from their previous role; the individuals still having the urge to do the work for their subordinates instead of delegating illustrate this. In the transition phase, the individuals in the study experienced the anxiety of wanting to make the new role a success whilst experiencing a sense of lack of belonging due to not being in the familiar old role and not entrenched in the new role. In the incorporation phase, the transitioning individuals experience a sense of stability where they are comfortable acting in the new role. Problem: This study aims to answer the question of how newly appointed team leaders in an automotive manufacturing organisation experience role transition from specialists to team leaders Method: The study will be employing the qualitative thematic deductive method. The target population consists of team leaders who have transitioned into the team leader position in the past two years in different departments. The data was collected by way of face-to-face semistructured interviews with a sample size of seven participants. Data analysis was conducted with a method that is consistent with thematic analysis. 3 Key Findings: Individuals transitioning have urgencies to perform their previous roles in the early phase; during the transition phase, they have anxiety because they are not yet successful in the new role, and in the final phase, they have become comfortable with their new roles and their new identities. Implications: The study's outcome is to identify insights and resultant recommendations for non-leading specialists transitioning into roles where they have to lead others. The study will add to the research in the field of leadership behaviour and organisational behaviour.
Keywords: Leadership; Automobile industry executives; Role expectation; Identity (Psychology); Personnel management; Organizational behavior